2019
DOI: 10.1042/cs20190873
|View full text |Cite
|
Sign up to set email alerts
|

Altered HDL metabolism in metabolic disorders: insights into the therapeutic potential of HDL

Abstract: Metabolic disorders are associated with an increased risk of cardiovascular disease (CVD), and are commonly characterized by a low plasma level of high-density lipoprotein cholesterol (HDL-C). Although cholesterol lowering medications reduce CVD risk in these patients, they often remain at increased risk of CVD. Therapeutic strategies that raise HDL-C levels and improve HDL function are a potential treatment option for reducing residual CVD risk in these individuals. Over the past decade, understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 128 publications
2
23
0
Order By: Relevance
“…On the other hand, HDL-C is a well-known protective factor for CVDs and exerts anti-inflammatory capacity in chronic diseases. [34,35] A recent study reported that the level of HDL-C was low in critically ill patients, which was significantly associated with disease severity. [36] Meanwhile, decreased level of HDL-C was found in patients with sepsis, which increased the risk of acute multiple organ failure and mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HDL-C is a well-known protective factor for CVDs and exerts anti-inflammatory capacity in chronic diseases. [34,35] A recent study reported that the level of HDL-C was low in critically ill patients, which was significantly associated with disease severity. [36] Meanwhile, decreased level of HDL-C was found in patients with sepsis, which increased the risk of acute multiple organ failure and mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, an increased TGto-CE ratio changes hydrophobic core fluidity and HDL functionality. In particular, these changes in HDL lipid composition affect apolipoprotein quality and quantity, determining a decrease of Apo-AI and Apo-AII levels [66] and altered HDL functionality by decreasing HDL-induced eNOS activation [67], HDL susceptibility to oxidation [18], and their antioxidant activity [68]. Indeed, HDL metabolism is substantially altered in dyslipidemic states.…”
Section: Obesitymentioning
confidence: 99%
“…HDL-C is a highly effective biomarker, which is considered to be inversely correlated with the risk of cardiovascular diseases and plays a crucial role in predicting adverse results [ 14 – 17 ]. However, as reported in the relevant literature, the classic HDL-C theory defined as the notion that intervention to increase HDL-C concentrations will vastly lessen the occurrence of adverse events is now being questioned [ 1 , 15 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%